2013
DOI: 10.1371/journal.pone.0054874
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of the Human TF-Glycome Provides a Structural Definition for the Specificity of Anti-Tumor Antibody JAA-F11

Abstract: Recombinant antibodies are of profound clinical significance; yet, anti-carbohydrate antibodies are prone to undesirable cross-reactivity with structurally related-glycans. Here we introduce a new technology called Computational Carbohydrate Grafting (CCG), which enables a virtual library of glycans to be assessed for protein binding specificity, and employ it to define the scope and structural origin of the binding specificity of antibody JAA-F11 for glycans containing the Thomsen-Friedenreich (TF) human tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…This is consistent with the crystallography and computational carbohydrate threading data, which show seven tyrosines (the labeling target of the iodogen method) to be in the binding site complementary determining regions [19]. Iodine labeling via the iodogen method sterically inhibited antigen binding.…”
Section: • Radiolabeling Of Jaa-f11 Via the Bolton-hunter Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the crystallography and computational carbohydrate threading data, which show seven tyrosines (the labeling target of the iodogen method) to be in the binding site complementary determining regions [19]. Iodine labeling via the iodogen method sterically inhibited antigen binding.…”
Section: • Radiolabeling Of Jaa-f11 Via the Bolton-hunter Methodssupporting
confidence: 87%
“…Cells producing this antibody were cultured in 5% ultra-low immunoglobulin fetal calf serum (GIBCO, Life Technologies, NY, USA) in Dulbecco's modified Eagle medium with added L-glutamine, sodium pyruvate and nonessential amino acids (Mediatech, VA, USA). JAA-F11 was purified using triple ammonium sulfate precipitation to 33.3% saturation followed by Cibacron Blue 3GA affinity chromatography (Sigma-Aldrich, MO, USA) [19]. [20].…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether a single glycan-binding interaction could involve both sites on each monomer, we performed MD simulations (Tessier et al, 2013) to sample sterically allowed configurations of glycan binding. Initially, we performed simulations of a small trisaccharide (Manα1-2Manα1-3Manα) bound to each binding site present on the BanLec monomer, and found that each site had a similar binding strength according to per-residue MM-GBSA (Molecular Mechanics/Generalized Born Surface Area) calculations (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Such a fragment of an oligosaccharide is often referred to as the minimal binding determinant (MBD). 26 In the case of 3TV3 and 3C6S, the MBDs are a disaccharide 66 and pentasaccharide, 67 respectively (Figure 2). Docking of the MBD generally improved the results (Table 3); however, an acceptable pose was only found in two of the five docking experiments for 3TV3, demonstrating the importance of multiple docking experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Structure-based analyses of antibody–carbohydrate or lectin–carbohydrate interactions offer an alternative means to guide affinity or specificity optimization. 17,25,26 …”
Section: Introductionmentioning
confidence: 99%